2021
DOI: 10.1002/ejhf.2198
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the monitoring of transthyretin amyloid cardiomyopathy

Abstract: Transthyretin amyloid cardiomyopathy (ATTR‐CM) is a life‐threatening condition with a heterogeneous clinical presentation. The recent availability of treatment for ATTR‐CM has stimulated increased awareness of the disease and patient identification. Stratification of patients with ATTR‐CM is critical for optimal management and treatment; however, monitoring disease progression is challenging and currently lacks best‐practice guidance. In this report, experts with experience in treating amyloidosis and ATTR‐CM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 69 publications
(160 reference statements)
0
73
2
2
Order By: Relevance
“…An increased amount of screening and awareness of ATTR-CM is needed to provide a complete and accurate perspective of the population with ATTR-CM diagnoses. 1 , 3 Until this occurs, tafamidis as a treatment of ATTR-CM may be underutilized, resulting in patient selection biases, and thus may affect available real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…An increased amount of screening and awareness of ATTR-CM is needed to provide a complete and accurate perspective of the population with ATTR-CM diagnoses. 1 , 3 Until this occurs, tafamidis as a treatment of ATTR-CM may be underutilized, resulting in patient selection biases, and thus may affect available real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of cardiac disease status should be part of a multiparametric evaluation. A consensus panel provided criteria of disease progression during therapy belonging to three categories [ 25 ]: (1) clinical and functional endpoints (any hospitalization for heart failure; any increase in New York Heart Association [NYHA] class; 10% decline in EQ-5D score; 40 m decrease in 6MWT); (2) biomarkers and laboratory markers (30% increase in NT-proBNP with 300 ng/L cut-off; 30% increase in high-sensitivity troponin; and (3) imaging and electrocardiographic parameters (left ventricle ejection fraction decrease > 5%; > 5 mL decrease in SV; ≥ 2 mm increase in left ventricle wall thickness; new-onset atrial fibrillation or atrioventricular block or bundle branch block; stepwise increase in diastolic dysfunction grade). The authors suggested using one marker from each category to assess response to therapy.…”
Section: Monitoring the Therapeutic Effectmentioning
confidence: 99%
“…Conversely, a partial response consistent in a reduction of 50% or more in concentrations of aberrant free light chains is not satisfactory [31] . It is known that renal dysfunction and gastrointestinal amyloid involvement may be associated with a worse prognosis and a higher rate of complications after ASCT [32] . For these reasons, it is mandatory to deeply evaluate all candidates for any gastrointestinal, hepatic, or renal involvement, including severe neuropathy or coagulopathy.…”
Section: Italian Datamentioning
confidence: 99%